2002
DOI: 10.1001/archpsyc.59.8.686
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch Negativity in Chronic Schizophrenia and First-Episode Schizophrenia

Abstract: The pitch-deviant MMN reductions present in patients with chronic schizophrenia are not present at first hospitalization. The sensory, echoic memory functions indexed by MMN seem unaffected early in the schizophrenia disease process. Reductions in MMN amplitude may develop over time and index the progression of the disorder, although that can only be definitively determined by longitudinal assessments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
166
5
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 261 publications
(196 citation statements)
references
References 66 publications
(76 reference statements)
22
166
5
1
Order By: Relevance
“…Deficits in early auditory sensory processing, including N1, MMN, and P300, have been shown using ERP in schizophrenic subjects (Baldeweg et al, 2004;Kasai et al, 2002;Salisbury et al, 1998;Javitt et al, 2000;Javitt et al, 1995;Elvevag et al, 2004), in prodromal subjects (Brockhaus-Dumke et al, 2005), and in SPD subjects (Salisbury et al, 1996;Niznikiewicz et al, 2000;Liu et al, 2007). Moreover, progressive changes in schizophrenic subjects can be indexed using a MMN paradigm in the ERP environment (Salisbury et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Deficits in early auditory sensory processing, including N1, MMN, and P300, have been shown using ERP in schizophrenic subjects (Baldeweg et al, 2004;Kasai et al, 2002;Salisbury et al, 1998;Javitt et al, 2000;Javitt et al, 1995;Elvevag et al, 2004), in prodromal subjects (Brockhaus-Dumke et al, 2005), and in SPD subjects (Salisbury et al, 1996;Niznikiewicz et al, 2000;Liu et al, 2007). Moreover, progressive changes in schizophrenic subjects can be indexed using a MMN paradigm in the ERP environment (Salisbury et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Auditory sensory processing has been found to be impaired in schizophrenia (Salisbury et al, 1998;Javitt et al, 2000) and correlate with clinical features, particularly negative symptoms (Javitt et al, 2000), (Kasai et al, 2002) (Leitman et al, 2005) and cognitive impairment (Baldeweg et al, 2004). Abnormalities in the superior temporal gyrus (STG) have been implicated in the processing of pure tones, a fundamental element of complex sounds and language, using fMRI (Wible et al, 2001) and event-related potentials (Salisbury et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with schizophrenia show stable, consistent deficits in MMN that also are associated with global assessment of everyday functioning [31]. Salisbury et al [32] showed that MMN deficits were not present in first-episode schizophrenia patients at initial assessment, but these deficits evolved over time. The possibility that MMN may be an index of later neurodevelopmental abnormalities in the early stages of schizophrenia suggests its potential utility in the study of the schizophrenia prodrome.…”
Section: Mismatch Negativity Paradigmmentioning
confidence: 99%